Increased Levels of Interleukin-10 and IgG3 Are Hallmarks of Indian Post-Kala-Azar Dermal Leishmaniasis - Ganguly, Sudipto; Das, Nilay Kanti; Panja, Moumita; Pal, Shekhar; Modak, Dolanchampa; Rahaman, Mehebubar; Mallik, Sudeshna; Guha, Subhashis Kamal; Pramanik, Netai; Goswami, Ramapada; Barbhuiya, Joyashree Nath; Saha, Bibhuti; et al. (The Journal of infectious diseases, 2008)
Background. Post-kala-azar dermal leishmaniasis (PKDL), an established sequela of visceral leishmaniasis (VL), is proposed to facilitate anthroponotic transmission of VL, especially during interepidemic periods. Immunopathological mechanisms responsible for Indian PKDL are still poorly defined. Methods. Our study attempted to characterize the immune profiles of patients with PKDL or VL relative to that of healthy control subjects by immunophenotyping, intracellular cytokine staining of peripheral blood mononuclear cells, and enzyme-linked immunosorbent assay for serum cytokines and immunoglobulin G (IgG) subclasses. Results. Patients with PKDL had significantly raised percentages of peripheral CD3+CD8+ cells compared with control subjects, a difference that persisted after cure. Patients with PKDL showed an intact response to phytohemagglutinin, with the percentages of lymphocytes expressing interferon (IFN)-γ, interleukin (IL)-2, IL-4, and IL-10 being comparable to those in control subjects. Patients with VL had decreased IFN-γ and IL-2 expression, which was restored after cure, and increased IL-10 expression, which persisted after cure. In their response to Leishmania donovani antigen, patients with PKDL showed a 9.6-fold increase in the percentage of IL-10-expressing CD3+CD8+ lymphocytes compared with control subjects, and this percentage decreased with treatment. Patients with PKDL had raised levels of IgG3 and IgG1 (surrogate markers for IL-10), concomitant with increased serum levels of IL-10. Conclusions. IL-10-producing CD3+CD8+ lymphocytes are important protagonists in the immunopathogenesis of Indian PKDL.